2013
DOI: 10.1371/journal.pone.0071718
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoiesis Suppression Is Associated with Anthrax Lethal Toxin-Mediated Pathogenic Progression

Abstract: Anthrax is a disease caused by the bacterium Bacillus anthracis, which results in high mortality in animals and humans. Although some of the mechanisms are already known such as asphyxia, extensive knowledge of molecular pathogenesis of this disease is deficient and remains to be further investigated. Lethal toxin (LT) is a major virulence factor of B. anthracis and a specific inhibitor/protease of mitogen-activated protein kinase kinases (MAPKKs). Anthrax LT causes lethality and induces certain anthrax-like s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 58 publications
0
33
0
Order By: Relevance
“…Our previous report revealed that LT suppressed erythropoiesis in bone marrow [15]. Following similar approaches [15], [25], we used surface expression of CD71 and TER-119 to verify the maturation status of various bone marrow erythroblasts under the G-CSF treatments with or without anthrax LT challenges.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous report revealed that LT suppressed erythropoiesis in bone marrow [15]. Following similar approaches [15], [25], we used surface expression of CD71 and TER-119 to verify the maturation status of various bone marrow erythroblasts under the G-CSF treatments with or without anthrax LT challenges.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous report revealed that LT suppressed erythropoiesis in bone marrow [15]. Following similar approaches [15], [25], we used surface expression of CD71 and TER-119 to verify the maturation status of various bone marrow erythroblasts under the G-CSF treatments with or without anthrax LT challenges. Although we found that G-CSF treatment rescued LT-induced erythrocytopenia (please see the following section), G-CSF pre-treatments could not overcome LT-mediated suppression on the cell numbers of both total erythroblast and individual subpopulations of erythroblast (R1 to R4 populations) (Figure 2C and 2D).…”
Section: Resultsmentioning
confidence: 99%
“…4,5,14,16,52,55,56 For cell and animal studies, high-performance liquid chromatography (HPLC)-purified LF and PA were reconstituted as LT in a ratio of 1:5, which resembles the ratio of PA and LF in the culture supernatants of B. anthracis. The LPS contamination was monitored using a Limulus Amoebocyte Lysate QCL -1000 kit (Lonza, Walkersville, MD, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The Abs used for ELISA (detecting soluble thrombomodulin) and flow cytometry (detecting endothelial surface TRAIL-R expression) analyses were anti-thrombomodulin Ig (Santa Cruz Biotechnology) and anti-TRAIL-R (1-4) Ig (R&D Systems), respectively. The endothelial cells were challenged with (+DENV) (multiplicity of infection [MOI] of 0.2, subcytotoxic) or without DENV (2DENV) in combination with or without preimmune Ig, anti-NS1 Ig, anti-NS1-DR4 Ig treatments (20 mg/ml, subcytotoxic; 24 and 48 h), and then the surface expression levels of TRAIL-Rs were analyzed by flow cytometry (FACSCalibur; BD Biosciences, San Jose, CA) (29)(30)(31). Fluorescence-labeled isotype-matched control Igs were used to determine the background staining levels in the flow cytometry analyses.…”
Section: Elisa and Flow Cytometrymentioning
confidence: 99%